Role of p57kip2 immunohistochemistry in the diagnosis and classification of molar pregnancies (Journal of Pathology of Nepal, 2025)
Background: Gestational trophoblastic disease is a group of benign and malignant disorders defined by abnormal trophoblastic proliferation, of which hydatidiform mole is the most common, characterized by hydropic swelling of placental villi and trophoblastic hyperplasia. It is imperative to further classify hydatidiform mole into complete mole and partial mole, as complete mole is associated with an increased risk of gestational trophoblastic neoplasia.Materials and Methods: This was a cross-sectional study carried out in the Department of Pathology, SGRRIM&HS, Dehradun. 51 clinically diagnosed cases of molar pregnancies (24 complete mole, 1 partial mole, 1 Hydatidiform mole-NOS and 24 non-molar products of conception were included in the study. Histomorphological features and the expression of IHC p57Kip2 (57P06) in cytotrophoblasts and villous stromal cells were studied.Results: Histomorphological assessment of the 51 cases showed 24/51 (47%) cases of complete mole, 1/51 (2%) case of partial mole, 2/ 51 (3.9%) cases with ambiguous histology diagnosed as Hydatidiform mole-NOS, and 24/51 (47.1%) cases of non-molar products of conception. The majority of the patients [36/51 (70.6%)] were in the 21-30 years age group. Expression of p57Kip2 was found to be corroborating with histomorphological diagnosis in 48/51 (94.1%) cases, diagnostic in 2/51 (3.92 %) of cases, and non-contributory in 1/51 (1.96%) cases.Conclusions: The study confirms that negative p57 IHC expression may reliably identify complete mole. However, immunohistochemistry has a limited role in discriminating partial mole from hydrops abortus and is also inconclusive in cases with discordant expression.